Incidence of active tuberculosis in individuals with latent tuberculosis infection in rural China: follow-up results of a population-based, multicentre, prospective cohort study. Issue 10 (October 2017) - Gao, Lei; Li, Xiangwei; Liu, Jianmin; Wang, Xinhua; Lu, Wei; Bai, Liqiong; Xin, Henan; Zhang, Haoran; Li, Hengjing; Zhang, Zongde; Ma, Yu; Li, Mufei; et al.
Summary: Background: The management of latent Mycobacterium tuberculosis infection is a new priority action for the WHO End Tuberculosis (TB) Strategy. However, national guidelines on latent tuberculosis infection testing and treatment have not yet been developed in China. Here, we present the results from the 2-year follow-up of a study that aimed to track the development of active disease in individuals with latent tuberculosis infection, identify priority populations for latent infection management, and explore the most suitable latent infection diagnostic approach. Methods: A population-based multicentre prospective study was done in four sites in rural China, between 2013 and 2015. The baseline survey in 2013 measured the prevalence of latent tuberculosis infection using QuantiFERON-TB Gold In-Tube (QFT) and tuberculin skin test (TST) in eligible participants. During the follow-up phase between 2014–15, we assessed individuals who had tuberculosis infection at baseline (QFT-positivity or TST tuberculin reaction size [induration] of ≥10 mm) for the development of active disease through active case finding. Eligible participants included in follow-up survey had a birth date before June 1, 2008 (5 years or older in 2013), and continuous residence at the study site for 6 months or longer in the past year. Participants with current active tuberculosis at baseline survey were excluded. Findings: Between Sept 1, 2013, and Aug 31, 2015, 7505 eligible participants (aged 5 years or older) were included in tuberculosis infection test positive cohorts (4455 were QFT positive, 6404 had TST induration ≥10 mm, and 3354 were positive for both tests) after baseline examination. During the 2-year follow-up period, 84 incident cases of active tuberculosis were diagnosed. Of participants who developed active tuberculosis, 75 were diagnosed with latent infection by QFT, 62 were diagnosed by TST, and 53 were diagnosed by both tests. An incidence rate of 0·87 (95% CI 0·68–1·07) per 100 person-years was observed for individuals who tested positive with QFT, 0·50 (0·38–0·63) per 100 person-years for those who tested positive with TST (p<0·0001), and 0·82 (0·60–1·04) per 100 person-years for those who tested positive with both tests. Male sex and a history of tuberculosis were significantly associated with increased risk of disease development with adjusted hazard ratios of 2·36 (95% CI 1·30–4·30) for male sex and 5·40 (3·34–8·71) for a history of tuberculosis. Interpretation: Our results suggest that high-risk populations in communities in rural China, such as individuals at a high risk of disease reactivation from previous tuberculosis, should be targeted for latent infection screening and treatment with an interferon-γ releasing assay rather than a TST. Funding: National Science and Technology Major Project of China, Program for Changjiang Scholars and Innovative Research Team in University of China, CAMS Innovation Fund for Medical Sciences, and Sanming Project of Medicine in Shenzhen.